Competition, competition law and the Malaysian financial sector - Abdul Rahman, Nasarudin; Ahamat, Haniff (2014)
ABSTRACT The main objective of competition law is to promote the process of competition and to ensure that market functions efficiently. The well-functioning of the market is important for vital economic development. However, competition does not always seem to work well in the financial system. This paper attempts to explore issues that may arise from the application of competition law in the Malaysian financial sector focusing on various forms of collaboration among market players. This paper argues that the cooperations or arrangements need to be assessed on case-by-case basis to see their actual effect on competition rather than treating them under the general object rule. In addition, a clear guidance should be formulated to avoid legal uncertainty and unpredictability.